Re-presenting the Orient: A Re-Orientalist Study of Khaled Hosseini’s The Kite Runner (2003) - Somia Sohail; Ayesha Siddiqa (University of Chitral Journal of Linguistics and Literature)
Diasporic writing is generally regarded as representative of the native people and their culture. In this regard, South Asia has been depicted in a variety of ways by writers of South Asian origins living in the West. While considered representatives of the South Asian tradition, diasporic writers’ depiction of the region, its people, and their culture has also come under scrutiny for reinforcing the East/West binary that reinstates the latter’ superiority. Khaled Hosseini is among those South Asian writers whose fiction is informed by his declaration “that Afghanistan is ‘my land of origin’” (Aubry, 2009, pp. 27-28); however, while Hosseini’s work has been a major source of information about Afghanistan for the West, at home, he is, at best, an ambivalent figure that has invited criticism pertaining to his representation of Afghanistan especially in his debut novel, The Kite Runner (2003). This article critically analyzes Hossini’s The Kite Runner through the lens of Lisa Lau’s theorization of re-Orientalism (2009) and bell hooks’s notion of patriarchal maleness to argue that the novel perceives the Afghan land and people through a patriarchal gaze that renders them inferior and subordinate, hence feminine vis-à-vis the superior, masculine, and patriarchal West. In this way, the novel ends up reinforcing the Orientalist project of perpetuating stereotypical images of the Orient. While previous scholarship mainly focuses on the development of the protagonist’s character through the themes of guilt, sin, and redemption in the novel, the uniqueness of this paper lies in its exploration of the text’s re-Orientalist proclivity. Critically analyzing the novel’s depiction of Afghanistan, its people, and culture, the paper argues that the text, through its patriarchal gaze, accords a superior place to maleness and reinforces the Western practice of feminizing the Orient.